Structural basis of host ligand specificity change of GII porcine noroviruses from their closely related GII human noroviruses - Yang Yang; Ming Xia; Leyi Wang; Sahaana Arumugam; Yajing Wang; Xianjin Ou; Chenlong Wang; Xi Jiang; Ming Tan; Yutao Chen; Xuemei Li (Emerging Microbes and Infections)
Diverse noroviruses infect humans and animals via the recognition of host-specific glycan ligands. Genogroup II (GII) noroviruses consist of human noroviruses (huNoVs) that generally bind histo-blood group antigens (HBGAs) as host factors and three porcine norovirus (porNoV) genotypes (GII.11/18/19) that form a genetic lineage lacking HBGA-binding ability. Thus, these GII porNoVs provide an excellent model to study norovirus evolution with host ligand specificity changes. Here we solved the crystal structures of a native GII.11 porNoV P protein and a closely-related GII.3 huNoV P protein complexed with an HBGA, focusing on the HBGA-binding sites (HBSs) compared with the previously known ones to understand the structural basis of the host ligand specificity change. We found that the GII.3 huNoV binds HBGAs via a conventional GII HBS that uses an arginine instead of the conserved aromatic residue for the required Van der Waals interaction, while the GII.11 porNoV HBS loses its HBGA-binding function because of two mutations (Q355/V451). A mutant that reversed the two mutated residues back to the conventional A355/Y451 restored the HBGA-binding function of the GII.11 porNoV P protein, which validated our observations. Similar mutations are also found in GII.19 porNoVs and a GII.19 P protein mutant with double reverse mutations restored the HBS function. This is the first reconstruction of a functional HBS based on one with new host specificity back to its parental one. These data shed light on the molecular basis of structural adaptation of the GII porNoVs to the pig hosts through mutations at their HBSs.